Seroprevalence of Toxoplasmosis in patients with chronic liver disease in Baghdad - Nafal, Raghad Hasan; Al-Warid, Harith Saeed; Al-Sultan, Hayder Jamal (Iraqi Journal of Science, 2019)
The influence of Toxoplasma gondii in the pathogenesis of hepatic disease has lately had considerable attention. The objective of this study is to assess the seroprevalence of T. gondii infection in patients with chronic liver disease from Baghdad-Iraq. All patients have attended Gastroenterology and Hepatology Teaching Hospital, Medical city in Baghdad, Iraq An analytical case–control study was achieved from September to November 2018. Seventy male patients with chronic liver disease (CLD) and 70 control males (free of chronic liver diseases) participated in this study, their ages were between (18-80) years old. Serum samples were taken from all subjects and were analysed with enzyme-linked immunosorbent assay (ELISA) for the presence of anti-T.gondii IgG and IgM antibodies. The prevalence of anti-T.gondii IgG was significantly higher 62.85% in CLD patients compared with 27.28% in the control subjects. Anti-T. gondii IgM antibodies were also showed to be significantly higher in CLD patients compared with control subjects. A significant relation between age and the prevalence of T.gondii was reported in this study. Toxoplasmosis was largely reported among those aged (˃40) years old for both CLD patients and control subjects, while the other age groups showed less seroprevalence rates. Sera samples for both CLD patients and control subjects were tested for different liver enzyme: aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP). ALT was greater in CLD-Toxoplasma positive patients comparing to CLD-Toxoplasma negative patients. In addition to AST was higher in control-Toxoplasma positive subjects comparing to control-Toxoplasma negative subjects. These findings show that Toxoplasmosis is high expected to be diagnosed with chronic liver disease patients. Consequently, attention would be focused on health education of peoples at high risk of toxoplasmosis.